Type II supernovae as distance indicators at near-IR wavelengths. Issue 4 (17th December 2018) - Rodríguez, Ó; Pignata, G; Hamuy, M; Clocchiatti, A; Phillips, M M; Krisciunas, K; Morrell, N I; Folatelli, G; Roth, M; Castellón, S; Jang, I S; Apostolovski, Y; et al.
ABSTRACT: Motivated by the advantages of observing at near-IR wavelengths, we investigate Type II supernovae (SNe II) as distance indicators at those wavelengths through the Photospheric Magnitude Method (PMM). For the analysis, we use BVIJH photometry and optical spectroscopy of 24 SNe II during the photospheric phase. To correct photometry for extinction and redshift effects, we compute total-to-selective broad-band extinction ratios and K -corrections up to $z$  = 0.032. To estimate host galaxy colour excesses, we use the colour–colour curve method with the V – I versus B – V as colour combination. We calibrate the PMM using four SNe II in galaxies having Tip of the Red Giant Branch distances. Among our 24 SNe II, nine are at cz > 2000 km s −1, which we use to construct Hubble diagrams (HDs). To further explore the PMM distance precision, we include into HDs the four SNe used for calibration and other two in galaxies with Cepheid and SN Ia distances. With a set of 15 SNe II we obtain an HD rms of 0.13 mag for the J -band, which compares to the rms of 0.15–0.26 mag for optical bands. This reflects the benefits of measuring PMM distances with near-IR instead of optical photometry. With the evidence we have, we can set the PMM distance precision with J -band below 10 per cent with a confidence level of 99 per cent.